RETRACTED: The role and molecular mechanism of Trop2 induced epithelial‐mesenchymal transition through mediated β‐catenin in gastric cancer - Wei Zhao; Lizhou Jia; Xingwang kuai; Qi Tang; Xiaochen Huang; Tingting Yang; Zhenning Qiu; Jin Zhu; Jianfei Huang; Wenbin Huang; Zhenqing Feng (Cancer Medicine)
Abstract The present study elucidates the potential role of Trop2 in tumor invasion and the promotion of epithelial‐mesenchymal transition (EMT) when binding β‐catenin in GC. The role of Trop2 in promoting EMT in GC cells was examined by a variety of experimental assays. Moreover, the underlying molecular mechanism of Trop2 in promoting EMT was studied by in vivo and in vitro assays. The Trop2 expression in relation to tumor metastasis status was detected by IHC in 248 cases of GC tissues and 86 cases of matched adjacent tissues. Trop2 promoted the metastasis and induces EMT in GC. Meanwhile, the elevated protein levels of Trop2 and mesenchymal markers were also found in the TGF‐β1‐induced EMT model in GC cells. Importantly, Trop2 physically bound and activated β‐catenin to promote EMT; moreover, Trop2 increased the accumulation of β‐catenin in the nucleus to accelerate metastasis in GC cells. Inhibition of Trop2 expression in GC cells prevented the migration and invasion of GC cells in vivo. Trop2+/vimentin+ expression was higher in GC tissues than that in matched adjacent tissues, and Trop2+/vimentin+ expression in GC was associated with the differentiation, TNM stage, and distant metastases. These sets of data reveal a novel regulatory network of Trop2 in EMT and GC metastasis, suggesting Trop2 as a useful marker for inducing EMT and metastasis of GC, which may help to lead a better understanding of the pathogenesis of the GC.